Determinants and Impacts of Trust on Awqaf Institutions: Intergenerational Evidence from Indonesia - Banu Muhammad Haidlir; Wahyu Jatmiko; A. Azizon; Rahmatina Awaliyah Kasri; Bambang Shergi Laksmono (Faculty of Economic and Business, 2023)
This study evaluates the determinants and impacts of trust toward awqf institutions. We extend previous studies by examining the determining role of religiosity and knowledge on trust towards awqf institutions, in addition to the role of reputation and integrity. Our study differs from the previous studies as we incorporate the intergenerational analysis of 658 experienced and inexperienced Indonesian waqf donors by employing the PLS-SEM method. Our findings suggest that religiosity and knowledge significantly influence trust toward awqf institutions. However, the impact differs across generations X, Y, and Z. While the direct impacts of religiosity and knowledge on the intention to do cash waqf are insignificant for certain generations, the variables significantly impact the intention of all generations when moderated by the trust. Therefore, our primary implication is for awqf institutions to know their customers better and offer more trust-enhancing programs for the inexperienced younger generations.JEL Classification: Z12, L31How to Cite:Haidlir, B. M., Jatmiko, W., Azizon, A., Kasri, R. A., & Laksmono, B. A. (2023). Determinants and Impacts of Trust on Awqf Institutions: Intergenerational Evidence from Indonesia. Etikonomi, 22(1), 175–196. https://doi.org/10.15408/etk.v22i1.26307.